High-resolution structures of HIV-1 Gag cleavage mutants determine structural switch for virus maturation - Mattei, Simone; Tan, Aaron; Glass, Bärbel; Müller, Barbara; Kräusslich, Hans-Georg; Briggs, John A. G. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
HIV-1 maturation occurs via multiple proteolytic cleavages of the Gag polyprotein, causing rearrangement of the virus particle required for infectivity. Cleavage results in beta-hairpin formation at the N terminus of the CA (capsid) protein and loss of a six-helix bundle formed by the C terminus of CA and the neighboring SP1 peptide. How individual cleavages contribute to changes in protein structure and interactions, and how the mature, conical capsid forms, are poorly understood. Here, we employed cryoelectron tomography to determine morphology and high-resolution CA lattice structures for HIV-1 derivatives in which Gag cleavage sites are mutated. These analyses prompt us to revise current models for the crucial maturation switch. Unlike previously proposed, cleavage on either terminus of CA was sufficient, in principle, for lattice maturation, while complete processing was needed for conical capsid formation. We conclude that destabilization of the six-helix bundle, rather than beta-hairpin formation, represents the main determinant of structural maturation.